Growth performance, gut morphology and immune response of broiler chickens fed low protein diets supplemented with lysine and methionine - Shazali, Nurhazirah (2015)
Protein is one of the important nutrients in feedstuff that needs to be met for the basic nutrient requirement of animals. The ideal protein concept contains all amino acids in the exact amount and proportion in order to maintain and fulfill the chicken’s requirements and at the same time reduce the feed cost. The present study was conducted to evaluate the effect of feeding a low crude protein diet with lysine and methionine supplementation on broiler performance. Two experiments were conducted in this study. In the first experiments, a total of 288 Cobb500 broiler chickens were used with 8 dietary treatments. The chickens were offered with a starter diet (21% to 18% crude protein) and finisher diet (18% to 15% crude protein) supplemented with three commercial amino acids (L-Lysine, DL-Methionine and L-Threonine). The amino acids in the starter and finisher diets from the different treatment groups were adjusted to similar levels. In continuation from the first experiment, the optimum level of the crude protein diet was used whilst the level of methionine and lysine was manipulated to the high, normal and low levels in the diets. Three hundred Cobb 500 chickens were used in this study with 10 treatments. The chickens were offered a starter diet that consisted of 1.4%, 1.2%, 1.0% lysine and 0.51%, 0.46%, 0.41% methionine in 19% crude protein; whereas the finisher diet contained 1.25%, 1.05%, 0.85% lysine and 0.48% 0.43%, 0.38% methionine in 16% crude protein diets. In the first experiment, reducing dietary crude protein by 2% with amino acid supplementation had a better growth performance, carcass composition, gut morphology and microflora than birds fed with commercial diet. The second experiment reported that high lysine and normal methionine levels in the diets had a greater growth performance, breast meat yield and liver weight as well as lower feed conversion ratio and abdominal fats. Increased methionine levels in the low crude protein diets showed a higher final body weight, weight gain, breast meat yield, liver weight and lower feed conversion ratio, abdominal fat. In conclusion, increasing 0.2% lysine level and maintaining methionine level supplementation in a dietary crude protein reduction by 2% is optimal for maximizing growth performance, absorptive capacity, and immune response in broiler chickens. In addition, it has been widely accepted that the case of the dietary protein level is an economic decision to be made by industrial companies to increase the cost effective benefits.